1986
DOI: 10.1128/aem.52.1.214-216.1986
|View full text |Cite
|
Sign up to set email alerts
|

Lethal effect of butylated hydroxyanisole as related to bacterial fatty acid composition

Abstract: Bacillus cereus, Clostridium perfringens, Staphylococcus aureus, Pseudomonas fluorescens, Pseudomonas fragi, Escherichia coli, and Salmonella "anatum" were challenged with butylated hydroxyanisole (BHA). Susceptibility was measured as the concentration of BHA required to cause a 90% reduction in bacterial survivors. Staphylococcus aureus LP and P. fragi were two of the most resistant species examined; C. perfringens and P. fluorescens were the most susceptible. Gram stain reaction was found not to be a strict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The PG‐induced increase in triazole antifungal activity, also observed with other imidazole drugs (Strippoli et al . 2000), suggests that one of the mechanisms of PG action might be an interaction with the membrane phospholipids, thus affecting molecular organization and favouring azole penetration into the membrane layer (Post and Davidson 1986). Furthermore, mitochondria are the critical targets for PG, and the toxicity of PG is related to inhibition of ATP‐synthesis with a PG concentration‐dependent mechanism (Nakagawa et al .…”
Section: Resultsmentioning
confidence: 99%
“…The PG‐induced increase in triazole antifungal activity, also observed with other imidazole drugs (Strippoli et al . 2000), suggests that one of the mechanisms of PG action might be an interaction with the membrane phospholipids, thus affecting molecular organization and favouring azole penetration into the membrane layer (Post and Davidson 1986). Furthermore, mitochondria are the critical targets for PG, and the toxicity of PG is related to inhibition of ATP‐synthesis with a PG concentration‐dependent mechanism (Nakagawa et al .…”
Section: Resultsmentioning
confidence: 99%
“…Monounsaturated fatty acids were the predominate species at 19 or 12C and synthesis of polyunsaturated fatty acids was highest at 12C. Post and Davidson (1986) reported that the ratio of saturated to unsaturated fatty acids of several pathogenic and spoilage bacteria, including S. aureus, did not account for the differences in susceptibility to butylated hydroxyanisole @HA) susceptibility among the test organisms. Different substrates were used for the organisms tested, however, and the cultures were incubated at temperatures ranging from 26 to 37C.…”
Section: Resultsmentioning
confidence: 99%